Argentina's Transport Privatization and Re-Regulation : Ups and Downs of a Daring Decade-Long Experience - Estache, Antonio 1957- (The World Bank, 1999)
November 1999 - Argentina's policy for reform of the transport sector has been a mix of competition in the market and, through concessions, for the market. Capacity has increased, demand has grown, and prices and services have improved. Public financing has not been eliminated but it has been drastically reduced. When Argentina initiated reform of its transport sector in 1989, it had few models to follow. It was the first Latin American country to privatize its intercity railroad, to explicitly organize intraport competition, and to grant a private concession to operate its subway. It was second (after Japan) to privatize its urban commuter railways and one of the first in the developing world to grant road concessions to private operators. Argentina's experience shows that transport privatization and deregulation provide efficiency gains that can be delivered to users. Despite unexpectedly high residual subsidy requirements, fiscal costs are lower, services have improved, and new investment is taking place. Argentina's decade-long experience shows that the reform process involves learning by doing. Inexperienced new regulators quickly face the challenges in controlling monopoly power and providing long-run incentives for private investment. Designing sustainable reform requires a commitment by government to minimize its role in the sector and to respect its original promises to both users and concessionaires. Argentina has learned the importance of building up the regulatory capacity needed to monitor contracts, especially when initial uncertainty about demand and cost conditions is strong and renegotiation is the probable outcome of daring reform. The government's main challenge in monitoring contracts is to get enough information to reach a balance in its decisions about distributing efficiency gains fairly between consumers and private investors.